Cardiac function is normal in most patients recovered from COVID-19. (14th October 2021) - Tangen, J; Aukrust, P; Barrat-Due, A; Troseid, M; Christoffer Olsen, I; Nezvalova-Henriksen, K; Kaasine, T; Dyrhol-Riise, A M; Rygh Holten, A; Finbraten, A K; Josefsen, T A; Lee, K C; et al.
Abstract: Background: There are conflicting results regarding impaired cardiac function in patients that have recovered from COVID-19. Cardiovascular magnetic resonance (CMR) studies have revealed a very high frequency of cardiac involvement (78%) and ongoing myocardial inflammation (60%) in patients recently recovered from COVID-19. Findings are advocating further investigation of the long-term myocardial consequences of COVID-19 disease. Purpose: We aimed to investigate left ventricular (LV) and right ventricular (RV) function by a comprehensive echocardiographic study in patients recovered from COVID-19 infection 3 months after admission to hospital. Methods: All patients (n=92) had been hospitalized for COVID-19 and were examined with echocardiography three months after hospitalization. They were 59±13 years, and 43% were women. LV function was assessed by ejection fraction (EF) and global longitudinal strain (GLS) and RV function was measured by fractional area change (FAC), tricuspid annular plane systolic excursion (TAPSE) and RV GLS free wall. Tricuspid regurgitation pressure gradient was measured to estimate pulmonary artery pressure. Results: LV EF was 63±6% and LV GLS was −18.6±2.2%. All patients had normal EF >53%, but 10 showed signs of subtle impaired LV function by LV GLS (≥ −16%). Only two of these did not have hypertension, LV hypertrophy, diabetes or other preexisting diagnosis of heart disease explaining subtle LV dysfunction. All had normal RV FAC (48±7%) and TAPSE (2.3±0.3 cm). We found modestly impaired RV longitudinal function (RV GLS free wall >−25%) in 30% patients, but none had RV GLS worse than −20%. One-third of all patients with reduced RV GLS had signs of elevated pulmonary arterial pressures, which might impact the assessment of RV function. Conclusions: Traditional echocardiographic parameters showed normal function in all hospitalized COVID-19 patients three months after hospital admittance. Approximately one-third had subtle ventricular dysfunction detected by sensitive echocardiographic methods, but these findings could mostly be explained by systemic or pulmonary hypertension. We cannot, however, exclude that a slight reduction in cardiac function in a minority of our patients was caused by the COVID-19 infection. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): National Clinical Therapy Research in the Specialist Health Services, Norway